Comparative Assessment of Heavy Metals in Water, Sediment and Adjacent Soil of Hudiara Drain: Heavy metals analysis - Ahmad, Farooq; Hafeez, Saba; Anjum, Fouzia; Munawar, Tayyaba (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Industrial effluents cause contamination of water resources especially when it is discharged untreated in waterways. This study was conducted to measure the concentration of different heavy metals (Chromium, Nickel, Lead, Manganese and Copper) in wastewater, sediment and irrigated soil. Samples were collected from Hudiara drain near Gajomatta, Lahore. Experiments were done for the identification of heavy metals concentration in samples. In first step acid digestion, using hot plate was done of all samples. In second step Heavy metals analysis was carried out using FAAS. In wastewater heavy metals was present in order of copper (28.01ppm) >Manganese (9.81ppm)>Nickel (0.79ppm)> Chromium (0.43ppm) >Lead (0.36ppm). In top soil the order was Copper (77.51ppm)> Manganese (9.93ppm)> Chromium (3.71ppm)> Nickel (0.71ppm) >Lead (0.57pm). In subsoil the heavy metal order was Copper (27.19ppm) >Manganese (11.94ppm) > Chromium (5.25ppm) Nickel (1.01ppm) >lead (0.61ppm). In sediment the heavy metals were observed as follows Manganese (8.43ppm)> Chromium (5.85ppm) > Copper (1.46ppm) > Nickel (0.89ppm) > Lead (0.79ppm). The results were compared with National Environment Quality Standards (NEQS) Pakistan, Canadian soil quality guidelines for agricultural soil and Canadian Sediment Quality Guidelines for the Protection of Aquatic Life (2002). Heavy metal contents of water and soil aretransferred to vegetables and crops, which cause serious health hazards on their consumption so industrial effluent should be treated at source.